Effectiveness of Video Learning Development Announcing - Fifit Fitriansyah (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
The learning process is the most important activity. Therefore, the success of achieving learning objectives depends on how the learning process takes place effectively. In improving the effectiveness of learning, one of them uses learning media in the form of learning videos. This study aims to see the effectiveness of the announcing learning video development model to improve student's learning outcomes. The research method used is research and development with qualitative descriptive data analysis techniques and descriptive statistical analysis. The assessment rubric is used as a performance assessment test to see learning outcomes. The results of this study indicate that student's learning outcomes after using announcing learning videos are as much as 84% increase compared to students who do not use announcing learning videos as much as 16%. Thus, the development of announcing learning videos is considered effective in improving student's learning outcomes.